Incorporating Woody Ornamentals into Residential Landscapes to Reduce Nutrient Leaching - Drew C. McLean; Andrew K. Koeser; Amy L. Shober; Zhixuan Qin; Gitta Hasing; Richard C. Beeson (EDIS)
Urban landscapes in Florida are typically dominated by turfgrass monoculture, with ornamental landscape plants comprising only a small portion of the landscape. Incorporating more woody ornamentals into your landscape can reduce fertilization and irrigation demand and help reduce nutrient leaching losses from your yard—a combination that will help protect Florida’s water resources. This 3-page fact sheet was written by Drew C. McLean, Andrew K. Koeser, Amy L Shober, Zhixuan Qin, Gitta Hasing, and Richard C. Beeson, and published by the UF Department of Environmental Horticulture, July 2014.